The Role of Heredity in Formation of a Person's Character (Based on Wilkie Collins’ Novel No Name) - Bohdan, Valerii; Poluliakhov, Artem (Berdyansk State Pedagogical University, 2022)
Topical scientific events, directly related to the existence of a human, could not but be reflected in prose fiction. Thus, Wilkie Collins’ novel raises the questions that are being discussed today both in the scientific literature and even in the general press around the world: What does our character depend on? Are character traits inherited? Does the environment affect personality development? Today, genetics has come close to explaining the phenomenon depicted in chapter one of the novel and developed in subsequent chapters – the complete dissimilarity of two siblings, both external and internal. The author wanted to explain this phenomenon, but he did not look for its causes in the area where they actually lie. He rejected their religious interpretation, but, at the same time, could not decisively break with the Christian myth: Evil – Good.
Роль спадковості у формуванні характеру людини (за романом Вілкі Коллінза «Без імені»)
У художніх творах не можуть не відображатись актуальні наукові події, безпосередньо пов'язані з існуванням людини. У романі У. Коллінза порушуються ті питання, які сьогодні обговорюються як у науковій літературі, так і навіть у широкій пресі всього світу: Від чого залежить наш характер? Чи успадковуються риси характеру? Чи впливає середа на розвиток особистості? Сьогодні генетика наблизилася до пояснення феномена, зображеного у першому розділі роману та розвиненого у наступних, – повної як зовнішньої, так і внутрішньої відмінності двох рідних сестер. Автор хотів пояснити цей феномен, але причини його шукав над тій сфері, де вони лежать насправді. Відкидаючи їх релігійне тлумачення, він у той самий час не зміг рішуче порвати з християнським міфом: Зло – Добро.
Keywords: character; personality development; heredity; genetics; характер; розвиток особистості; спадковість; генетика